The Contribution of Indonesian International Student Mobility Awards (IISMA) on the Development of Employability Skills of Undergraduate Students in Indonesia - Dewanto, Nadira; Pritasari, Adita (Journal Integration of Management Studies, 2023)
Indonesia has the second highest youth unemployment rate among all ten ASEAN countries according to The World Bank Data in 2021, with 12% of the total unemployment rate dominated by bachelor graduates. One of the reasons behind youth unemployment in Indonesia is the mismatch between the skills possessed by university students and the labor market skills demand, referred to as the "skill gap." Experts believe that such a high number of youth unemployment is often linked to the failure of educational institutions to develop graduates with employability skills. Moreover, the skills gap is also associated with globalization in the 21st century, followed by new government regulations that ease hiring foreign workers in Indonesia. In this era, Indonesian graduates have to compete with employees from foreign countries, thus making international and multicultural knowledge desired by companies. To tackle these challenges posed by globalization and the quality of education, many higher education and government institutions are implementing one of the most prominent forms of internalization,  international student mobility programs, hoping to prepare bachelor graduates to be more competitive internationally. In 2021, the Indonesian government displayed its effort to prepare Indonesian graduates to possess valuable workplace skills in the 21st century through funded international student mobility, namely IISMA (Indonesian International Student Mobility Awards). However, despite the enormous efforts of implementing the program, there are still many contra-arguments from higher education institutions and Indonesian society regarding the contribution of IISMA in developing the employability skills of undergraduate students. This study is aimed to identify the contribution of IISMA di developing the employability skills of undergraduate students in Indonesia and to see whether it has a difference with the development of employability skills in regular Indonesian undergraduate programs. This study used a qualitative approach using semi-structured interviews with the interviewees from Universitas Indonesia, Institut Teknologi Bandung, and Universitas Gadjah Mada, who completed an IISMA program in 2021 and 2022. The study discovered that most employability skills desired by companies are mainly developed during the IISMA program compared to an undergraduate program in Indonesia.